高油酸葵花籽油酶促酯交换制备中长链 甘油三酯的工艺研究Preparation of medium- and long- chain triglycerides by enzymatic transesterification of high oleic acid sunflower seed oil - 吴凡1，杨博1，郭嘉2 WU Fan1，YANG Bo1，GUO Jia2 (Zhongguo youzhi)
旨在为开发健康油脂提供参考，利用脂肪酶Lipozyme RM IM催化高油酸葵花籽油与椰子油合成中长链甘油三酯（MLCT）。采用单因素试验和响应面试验对MLCT的合成条件进行优化，并对原料油与最佳工艺条件下制得的产品脂肪酸组成进行对比。结果表明：最佳的MLCT合成工艺条件为反应温度61 ℃、反应时间6.2 h、酶用量9.3％、底物配比6∶ 4（椰子油与高油酸葵花籽油物质的量比），在此条件下产品中MLCT含量为75.98％；产品中主要脂肪酸为油酸（42.711%）和月桂酸（26.226%）。综上，制备的产品中富含MLCT，有较大的市场应用潜力。In order to provide references for the development of healthy fats and oils, the medium-and long-chain triglycerides (MLCT) was synthesized from high oleic acid sunflower seed oil and coconut oil catalyzed by the lipase Lipozyme RM IM, and the synthesis conditions of MLCT were optimized using single factor test and response surface test. The fatty acid compositions of the raw oils were compared with the product produced under the optimal process conditions. The results showed that the optimal MLCT synthesis conditions were reaction temperature 61 ℃, reaction time 6.2 h, enzyme dosage 9.3%, and substrate ratio 6∶ 4 (molar ratio of coconut oil to high oleic acid sunflower seed oil). Under the optimal conditions, the MLCT content was 75.98%, and the main fatty acids in the product were oleic acid (42.711%) and lauric acid (26.226%). In conclusion, the prepared product is rich in MLCT and has a large potential for market application.